Juggling Aquaculture Intellectual property (IP): The Balance between Innovation and Access in Developing and Developed Countries, Anchored by US-India Case Studies - Sadhu, Maitrayae; Golder, Papiya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Intellectual property rights are intangible rights which are attributed to the creator of a property which belongs to the mind, intellect and skills of the creator. Intellectual property (IP) rights are critical in the field of aquaculture, particularly when it comes to incentivizing the development and use of genetically modified (GM) species. These rights provide protection to innovators who have invested significant time, expertise, and resources into creating GM aquatic organisms. This study aims to addresses the challenges that developing countries face in protecting the IP rights in aquaculture field. The United States employs a comprehensive and inclusive strategy on biotech patents to promote innovation, but India enforces more stringent restrictions to balance scientific progress with ethical and societal considerations. This difference illustrates a wider chasm between wealthy and developing nations, as the latter frequently confront hazards of exploitation and insufficient acknowledgment of traditional knowledge and ecological contributions.